The Effect of Profitability, Liquidity and Solvency on Corporate Social Responsibility - Yunita Easty Pertiwi Lolo; Willy Sri Yuliandhari (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2020)
CSR is an obligation of a company that not only provides the needs of the community but also pays attention how to maintain environmental quality positively contributing to the communities in which the company operates. Because it is a index Sri-Kehati generally consists of companies that are already stable and have good performance. With increasing public awareness of the company’s environment, it is demanded to have responsibility for operational activities carried out not only by focusing on the profits generated, howover, based on a survey conducted at the Research Center for Governance, Institutions, and National University Singapore (NUS) Business School shows lack of companies understanding of CSR practices especially in Indonesia (CNN Indonesia, 2016). The purpose of this research is to find out several factors that influence CSR practices so that the variable in this study are CSR disclosure and the independent variables are profitability (net profit margin), liquidity (current ratio) and solvency (debt to total asset). The sample of this study was 60 sample consisting of companies listed on the Sri-Kehati index in the 2015-2018 using data panel regretion with the help of Eviews10 application with quantitative methods. The result of this study indicate that simultaneous profitability (net profit margin), liquidity (current ratio), and solvency (debt to total asset) affect CSR disclosure. Partially profitability (net profit margin), liquidity (current ratio, and solvency (debt to total asset ratio) affects the disclosure of CSR with the ability of independent variables explain the dependent variable at 66,51%. The company is expected to be able to control the use of debt of a source of funding and reduce the use of expenses so that operational activities do not depend on debt.